Multi-Territorial Ischemic Stroke with Hemorrhagic Transformation and Secondary Staphylococcus hominis Septicemia: A Comprehensive Neuro-Critical Case Analysis - Jeremy J. O. Tobing; Maria Monasias Nataliani; Abraham Daryl Rustandar (International Medical Journal Corp. Ltd, 2026)
BACKGROUND Acute ischemic stroke involving multiple vascular territories (multi-territorial) presents a significant clinical challenge with high morbidity and mortality rates.1 This condition is often exacerbated by severe acute hypertensive responses, which increase the risk of hemorrhagic transformation (HT).3 Beyond the primary neurological injury, intensive care unit (ICU) patients are highly susceptible to nosocomial infections that can trigger systemic sepsis.5 Staphylococcus hominis, a member of the Coagulase-Negative Staphylococci (CoNS) group, is increasingly recognized as a relevant opportunistic pathogen in critically ill and immunocompromised patients.5 CASE REPORT A 54-year-old female (Mrs. PS) presented with sudden loss of consciousness (GCS 3-4) and a hypertensive crisis (240/150 mmHg). Head CT scan revealed extensive multi-territorial cerebral infarction involving the left parietotemporal cortical-subcortical area, right cerebellum, and bilateral basal ganglia, accompanied by signs of hemorrhagic transformation and ventriculomegaly. The patient was admitted to the ICU with mechanical ventilator support and aggressive blood pressure control. During treatment, the patient's clinical condition deteriorated, and blood cultures identified the growth of methicillin-resistant Staphylococcus hominis ssp hominis (MRCoNS). Despite intensive resuscitation and stabilization efforts, the patient passed away on the fifth day of care due to cardiac and respiratory arrest. DISCUSSION Analysis of this case highlights the interaction between autonomic dysregulation following a severe stroke (NIHSS score 29) and systemic failure.9 The high NIHSS score and low GCS at admission are powerful predictors of in-hospital mortality.10 The emergency hypertension likely contributed to the hemorrhagic transformation through blood-brain barrier disruption.13 The discovery of S. hominis in blood cultures complicated clinical management; although often considered a contaminant, the consistent growth pattern (4 out of 4 bottles) and resistance to oxacillin and linezolid indicated a true pathogenic role in worsening the prognosis through nosocomial sepsis.14 Blood pressure management was tailored to balanced guidelines, targeting a systolic blood pressure (SBP) of 160-180 mmHg to stabilize the HT while maintaining cerebral perfusion.16 CONCLUSION This case reinforces that multi-territorial stroke with an extremely high NIHSS score carries a very poor prognosis.18 Management requires an aggressive multidisciplinary approach to control hemodynamic parameters, cerebral edema, and to prevent or treat nosocomial infections.20 Early recognition of multi-drug resistant pathogens like Staphylococcus hominis is crucial in determining therapeutic success in the ICU environment.22